ADOPTION OF SCIENTIFIC PRACTICES AMONG DAIRY FARMERS – AN EXPLORATORY STUDY IN KARNATAKA - E. MUTTURAJ YADAV; M. KIRAN, PAVAN BELAKERI, GK.CHANDRASEKAR, V. JAGADEESWARY, K. SATYANARAYAN (The Journal of Research, PJTSAU, 2017)
Livestock plays an important role in socioeconomic development and to the growth of national economy. The contribution of livestock sector to the national economy in terms of Gross Domestic Product (GDP) is 4.1 percent and it makes up to 25 percent of the total value of output of agriculture and allied sector at current price during 2012-13 (BAHFS, 2014). Livestock activities have contributed to the food basket, nutrition security and household income of the farmers and play a significant role in generating gainful employment in the rural areas. India, the largest producer of milk in the world, produces over 140 million tonnes of milk (NDDB, 2014) and is contributing to more than 17 percent of global milk production.